Schism Seventh-Day Adventism in Post-Denominational China - Chow, Christie Chui-Shan 1967- (Liu Institute Series in Chinese Christianities, 2021)
"Scholars have been slow to consider Chinese Protestantism from a denominational standpoint. In Schism, the first monograph that documents the life of the Chinese Adventist denomination from the mid-1970s to the 2010s, Christie Chui-Shan Chow explores how Chinese Seventh-day Adventists have used schism as a tool to retain, revive, and recast their unique ecclesial identity in a religious habitat that resists diversity. Based on unpublished archival materials, fieldwork, oral history, and social media research, Chow demonstrates how Chinese Adventists adhere to their denominational character both by recasting the theologies and faith practices that they inherited from American missionaries in the early twentieth century and by engaging with local politics and culture. This book locates the Adventist movement in broader Chinese sociopolitical and religious contexts and explores the multiple agents at work in the movement, including intrachurch divisions among Adventist believers, growing encounters between local and overseas Adventists, and the denomination’s ongoing interactions with local Chinese authorities and other Protestants. The Adventist schisms show that global Adventist theology and practices continue to inform their engagement with sociopolitical transformations and changes in China today. Schism will compel scholars to reassess the existing interpretations of the history of Protestant Christianity in China during the Maoist years and the more recent developments during the Reform era. It will interest scholars and students of Chinese history and religion, global Christianity, American religion, and Seventh-day Adventism."--